2022
DOI: 10.17509/ijost.v8i2.54794
|View full text |Cite
|
Sign up to set email alerts
|

Design of Robust Control for Vehicle Steer-by-Wire System

Abstract: This study presented the design of a robust controller based on Integral Sliding Mode Control (ISMC) for controlling the Vehicle Steer-by-Wire (VSbW) system. The dynamic model of the VSbW system is first developed and then the design of ISMC has been conducted via the states of the system. The VSbW system has been described by two terms; one term represents the nominal model, which is free from nonlinearities, and the other term lumps the uncertainties in system parameters. The integral sliding mode controller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Design is a plan or drawing produced to show the look and function or workings of a project or other object before it is made (Shahid et al, 2019;Husain et al, 2023). The activity began with coming up with the idea and later proceeded to scriptwriting with a draft and sketch of the task and content coverage of the model .…”
Section: Resultsmentioning
confidence: 99%
“…Design is a plan or drawing produced to show the look and function or workings of a project or other object before it is made (Shahid et al, 2019;Husain et al, 2023). The activity began with coming up with the idea and later proceeded to scriptwriting with a draft and sketch of the task and content coverage of the model .…”
Section: Resultsmentioning
confidence: 99%
“…Future extension of this study, one cannn suggest other control strategies to suspend the motion of heart impeller and a comparison study can be conducted between the proposed controller and these suggested controllers [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Several sliding mode controller strategies have been proposed to address these challenges, including the integral sliding mode controller (ISMC) strategy, which eliminates the reaching phase by enforcing the system state to be on the sliding manifold from the beginning through an equivalent controller [27,28]. Notably, the ISMC does not alter the system order [29]. However, both the SMC and ISMC suffer from chattering, necessitating approximations to mitigate the issue [30].…”
Section: Introductionmentioning
confidence: 99%